Screening of opportunistic microbes from the infected sites of oral cancer patients and a study of their antibiotic resistance pattern - Nawar, Zareen (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.